2015
DOI: 10.1128/aac.04624-14
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Skin and Nasal Povidone-Iodine Preparation against Mupirocin-Resistant Methicillin-Resistant Staphylococcus aureus and S. aureus within the Anterior Nares

Abstract: [BN]) or left untreated. One hour posttreatment, explants were washed with phosphate-buffered saline (PBS) plus 2% mucin. One, 6, or 12 h later, bacteria were recovered and enumerated. Alternatively, following baseline sampling, human subjects applied two consecutive applications of SNP or saline to their anterior nares. One, 6, and 12 h after application of the preparation (postprep), nasal swabs were obtained, and S. aureus was enumerated. We observed that treatment of infected PM or human skin explants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 63 publications
0
46
0
1
Order By: Relevance
“…The future for S. aureus decolonisation may be improved by the use of effective iodine or chlorhexidine based agents, that avoid the potential for the emergence of antibiotic resistance, and can be used as a single application. 16 Guidelines: While both the WHO and the CDC provide no recommendations regarding the pre-operative screening for S. aureus, the WHO recommend using mupirocin 2% for treating known nasal carriers (strong recommendation). 6 They do not recommend for or against the use of a chlorhexidene body wash for the purpose of decolonisation.…”
Section: Pre-operative Measuresmentioning
confidence: 99%
“…The future for S. aureus decolonisation may be improved by the use of effective iodine or chlorhexidine based agents, that avoid the potential for the emergence of antibiotic resistance, and can be used as a single application. 16 Guidelines: While both the WHO and the CDC provide no recommendations regarding the pre-operative screening for S. aureus, the WHO recommend using mupirocin 2% for treating known nasal carriers (strong recommendation). 6 They do not recommend for or against the use of a chlorhexidene body wash for the purpose of decolonisation.…”
Section: Pre-operative Measuresmentioning
confidence: 99%
“…One implementation challenge is monitoring both patient compliance with the mupirocin treatment regimen and patient tolerance of the application 12 . In studies on high‐level mupirocin resistance, widespread use of mupirocin repeatedly applied to wounds (eg, dialysis catheter exit sites, decubitus ulcers) has been associated with mupirocin resistance and treatment failures 2,13 . Deeny et al 14 studied mupirocin resistance in MRSA strains in clinical‐use scenarios and found that the prevalence of mupirocin resistance increased 50% to 75% during universal decolonization and increased 10% during targeted decolonization.…”
Section: Continuing Education: Clinical Issuesmentioning
confidence: 99%
“…An alternative to nasal decolonization is the use of an antiseptic such as 5% povidone‐iodine 13,16‐18 or an alcohol‐based antiseptic (eg, 70% ethanol) 19,20 . Use of an antiseptic may be advantageous for universal decolonization because there is less concern for antibiotic resistance.…”
Section: Continuing Education: Clinical Issuesmentioning
confidence: 99%
See 2 more Smart Citations